PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA MELALUI METODE PENEMUAN TERBIMBING BERBANTUAN SOFTWARE GEOGEBRA PADA MATA KULIAH KALKULUS PEUBAH BANYAK DI FKIP UMSU - Ismail Hanif Batubara (MES: Journal of Mathematics Education and Science, 2019)
Abstract. The purpose of this study was to find out: (1) Is the increase in mathematical critical thinking abilities of students given the guided discovery method assisted by Geogebra software higher than students who were given guided discovery method learning without Geogebra software, (2) Are their interactions between learning with students 'initial mathematical abilities towards improving students' critical thinking skills. This research is a quasi-experimental study. The population of this study is that all classes in the fourth-semester mathematics education study program are approximately 120 people. Randomly, two classes were chosen from four classes. The experimental class was treated with Geogebra assisted guided discovery methods and the control class was treated with a guided discovery method without the help of Geogebra. Data analysis was performed by analysis of two-way variance (ANAVA). The results showed (1) Improvement of mathematical critical thinking skills of groups of students who obtained guided discovery method learning using GeoGebra software was higher than the group of students who received learning through guided discovery methods without GeoGebra software. (2) There is no interaction between the learning model and the initial ability of students in improving students' critical thinking skills in mathematics.Keywords: Critical Thinking Ability, Guided Discovery Method, Geogebra